ANALISIS PRAKTIK PENGASUHAN ORANG TUA DALAM MENDUKUNG PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI - Rahmah R Aisy; Imamah (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study was conducted to analyze parental caregiving practices in supporting the social-emotional development of early childhood at TK Negeri 3 Banda Aceh through a case study approach. The research focused on two children with different parenting backgrounds and social experiences to understand how family communication patterns, emotional regulation, and social environments influence children’s social-emotional development. Data were collected through observation, in-depth interviews, and documentation involving parents and teachers as the primary data sources. The findings revealed that warm and responsive caregiving interactions support children’s ability to engage in social interactions, regulate emotions, and develop self-confidence. In contrast, limited communication stimulation and unstable family social environments affect children’s social adaptation abilities. However, the study also found that the school environment, teacher-child relationships, and peer interactions function as protective factors that help support children’s social-emotional development despite less optimal caregiving practices at home. These findings indicate that the quality of early childhood social-emotional development is strongly influenced by the consistency of family interaction patterns, support from the school environment, and children’s daily social experiences. This study contributes to the development of a more holistic early childhood education approach that emphasizes children’s emotional well-being.